Christ the Lord : [compact disc, unabridged] : the road to Cana / Anne Rice. - Rice, Anne, 1941- (Random House Audio, 2008)
A fictional account of the life of Christ beginning prior to his baptism in the Jordan River and concluding with the miracle at Cana, as he leaves his everyday life in Nazareth to confront his destiny.